2017
DOI: 10.1371/journal.pone.0179724
|View full text |Cite
|
Sign up to set email alerts
|

Transient effects of transfusion and feeding advances (volumetric and caloric) on necrotizing enterocolitis development: A case-crossover study

Abstract: ObjectiveTo evaluate the short-term effects of feed fortification, feed volume increase, and PRBC transfusion on the odds of developing NEC.Study designCase-crossover study of neonatal intensive care infants born at ≤ 32 weeks’ gestation who were admitted to 5 central Ohio intensive care units from January 2012-July 2016 and developed NEC Bell Stage ≥2. Each patient served as their own control, with exposure during the 48-hour period just prior to NEC onset (hazard period) being compared to a preceding 48-hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…Similar to our research, in the study by VT Le in case-crossover research for assessment of the NEC and the forti cation and volume increase of milk, in 63 preterm infants<32 weeks of gestation, they did not detect any effect of the forti cation and volume of the milk and GI problems (14), inversely some other studies such as Alfaleh showed that PCT was associated with the lower rate of NEC in preterm infants (15).…”
Section: Discussionsupporting
confidence: 90%
“…Similar to our research, in the study by VT Le in case-crossover research for assessment of the NEC and the forti cation and volume increase of milk, in 63 preterm infants<32 weeks of gestation, they did not detect any effect of the forti cation and volume of the milk and GI problems (14), inversely some other studies such as Alfaleh showed that PCT was associated with the lower rate of NEC in preterm infants (15).…”
Section: Discussionsupporting
confidence: 90%
“…In line with the present research, a case-crossover study by Le VT et al on NEC, milk fortification, and milk volume increase showed that milk fortification and volume had no associations with GI problems in 63 preterm infants < 32 weeks of gestation (15). Conversely, some other studies, including the one conducted by Alfaleh et al, showed that PCT was associated with a lower rate of NEC in preterm infants (16).…”
Section: Discussionsupporting
confidence: 89%
“…All these measures are indicative of confounding as these may be related to delayed introduction or interruption of feeds and are themselves associated with development of NEC. Therefore, certain authors argue that the risk of NEC should not be considered in isolation of other potential clinical outcomes while formulating feeding policies and practices for preterm infants [ 20 ]. Clinical studies have evaluated the effects of different feeding regimens on the incidence of NEC and outcomes in premature neonates [ 21 ].…”
Section: Discussionmentioning
confidence: 99%